Strategic design of strained heterostructure anode for large-area AEM water electrolyzer via a facile etching method - Kumar, Sonu; Selvaraj, Kaliaperumal (ACS Applied Energy Materials, 2026)
Iron-based doped catalysts and various heterojunctions have been extensively studied for the Oxygen Evolution Reaction (OER). However, our understanding of the structural properties of these catalysts remains limited. Additionally, most studies have been conducted on a small scale, which restricts their practical application and potential. In this work, we designed an interface composed of Fe-doped Ni3S2 and FeOOH (FNS/NF) to function as an anode for a larger-area Anion Exchange Membrane Water Electrolyzer (AEMWE) cell. This was accomplished using the electrodeposition and electroless deposition methods at room temperature. The FNS/NF anode achieves a current density of 1 A cm-2 when paired with a standard catalyst (Pt/C) cathode, outperforming current state-of-the-art configurations that reach only 0.91 A cm-2. Furthermore, the FNS/NF anode attains over 1.3 A cm-2 when combined with our already published nonprecious metal cathode (rNSMA). This configuration exhibits a degradation rate of 1.2 mV/h after more than 100 h of stability testing, accompanied by an impressive cell efficiency of 85.40% and an energy efficiency of 38.98 kWh/kg. Comprehensive characterizations were conducted to gain a deeper understanding of the catalyst's phase characteristics, revealing that iron is in the +3 oxidation state in both FeOOH and Fe-doped Ni3S2, which forms a heterojunction. The FeOOH on the surface helps reduce the overpotential, while the Fe-doped Ni3S2 sustains performance for a longer duration.
Keywords: AnionExchange Membrane Water Electrolyzer (AEMWE); Compressive Strain; interface; Iron Oxyhydroxide; Iron-doped Nickel Sulfide; OER